HISTORY, PHYSIOLOGY AND MODERN APPROACHES TO THE TREATMENT OF INTRA-ABDOMINAL HYPERTENSION AND ABDOMINAL COMPARTMENT SYNDROME - Мартынов, Александр Анатольевич; Баранов, Андрей Игоревич; Лещишин, Ярослав Миронович; Кемеров, Сергей Викторович (Medicine in Kuzbass, 2017)
The article provides information about the history of the study of intraabdominal pressure, the formation of the concept of abdominal compartment syndrome and its pathophysiological features. It also provides recommendations for the treatment of this severe syndrome.
Keywords: intra-abdominal pressure; intra-abdominal hypertension; abdominal compartment syndrome; decompressive laparotomy